CRISPR, an innovation in the field of gene editing. Proposing a way to include it in a public health system - Kolisis (Νικόλαος Κολίσης), Nikolaos (Bioethica, 2020)
The invention of CRISPR technology and its current and potential applications have been a subject of controversy among scientists, philosophers and legal theorists. After taking under consideration the current discussion concerning the use of CRISPR for editing human genome the article treats the question of a wider offer of CRISPR-based therapies from a Public Healthcare system and proposes method for a fair and financially sustainable way for adopting the new possibilities this new tool has to offer.